Assessment of the prevalence of burnout syndrome in employees of a Hotel in Lima - Orozco, Fiorella (2024)
Human resources are a differentiating element in hotel companies, due to their high interpersonal interaction. This interaction produces chronic stress, the main cause of Burnout Syndrome (BS), whose dimensions are emotional exhaustion, depersonalization, and personal fulfillment. This study aims to assess the prevalence of Burnout Syndrome in frontline employees of a Hotel in Lima (Peru). To this end, the prevalence of BS is analyzed in its dimensions, considering sociodemographic and labor factors. It was adopted a quantitative methodology. In this study, 46 employees were surveyed, applying the MBI-ES inventory (Maslach Burnout Inventory – Spanish version). The results showed that 19.6% have high levels of BS, which 77.4% are first-line employees and 15.2% present a medium level of BS. The BS is more highlighting in young women between the ages of 20 and 30 and in those who receive a lower salary range. Furthermore, correlation tests showed that the Burnout Subscales are strongly and significantly related.